Platelet dysfunction after normothermic cardiopulmonary bypass in children: Effect of high-dose aprotinin - Flaujac, Claire; Pouard, Philippe; Boutouyrie, Pierre; Emmerich, Joseph; Bachelot-Loza, Christilla; Lasne, Dominique (Thrombosis and Haemostasis, 2007)
Platelet dysfunction after cardiopulmonary bypass (CPB) can contribute to excessive post-operative bleeding. Most trials of the protective effect of aprotinin in this setting have involved hypothermic CPB, which is more deleterious for platelets than normothermic CPB.Here we investigated the effect of aprotinin on platelet function during normothermic CPB in pediatric patients. Twenty patients (9 newborns [<1 month old] and 11 infants [<36 month old]),weighting less than 15 kg and undergoing normothermic CPB (35–36°C) were randomly assigned to two equal groups,one of which received high-dose aprotinin.Platelet function was assessed by flow cytometry just before CPB and 5 minutes after heparin neutralization. F1+2 fragments were measured by ELISA before and 5 minutes after CPB. Platelet activation marker expression (CD62P and activated αIIbβ3) induced by ADP or TRAP was lower after CPB than before CPB, suggesting a deleterious effect of normothermic CPB on platelet function. Prothrombin fragment F1+2 levels increased after CPB. Aprotinin administration did not influence the level of prothrombin fragments or platelet marker expression measured in basal condition. However, after CPB, the capacity for platelet activation was higher in the aprotinin group, as shown by measuring CD62P expression afterTRAP activation (p=0.05).This study suggests that pediatric normothermic CPB causes platelet dysfunction, and that high-dose aprotinin has a protective effect.
Keywords: Aprotinin; cardiopulmonary bypass; platelet; pediatric cardiac surgery